Evaluation of saffron (Crocus sativus L.) adulteration with plant adulterants by 1H NMR metabolite fingerprinting. (15th April 2015) - Petrakis, Eleftherios A.; Cagliani, Laura R.; Polissiou, Moschos G.; Consonni, Roberto
Abstract : Graphical abstract: Highlights: NMR based metabolite fingerprinting for saffron quality characterisation. Differentiation between authentic and adulterated saffron. Identification of common plant adulterants at minimum level of 20% (w/w). Abstract: In the present work, a preliminary study for the detection of adulterated saffron and the identification of the adulterant used by means of 1 H NMR and chemometrics is reported. Authentic Greek saffron and four typical plant-derived materials utilised as bulking agents in saffron, i.e., Crocus sativus stamens, safflower, turmeric, and gardenia were investigated. A two-step approach, relied on the application of both OPLS-DA and O2PLS-DA models to the 1 H NMR data, was adopted to perform authentication and prediction of authentic and adulterated saffron. Taking into account the deficiency of established methodologies to detect saffron adulteration with plant adulterants, the method developed resulted reliable in assessing the type of adulteration and could be viable for dealing with extensive saffron frauds at a minimum level of 20% (w/w).